POLA ASUH DAN STATUS GIZI BALITA DI KECAMATAN LAPE, KABUPATEN SUMBAWA, NUSA TENGGARA BARAT - Apriyanto, Denny; Subagio, Hertanto Wahyu; Sawitri, Dian Ratna (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The purpose of this study was to investigate the relationship between caregiving behavior and nutritional status of under five children. This research used the quantitative cross-sectional design. The number of samples were 70 mothers taken by a multistage random sampling. The data was gained through in-depth interview and observation. Nutritional status was obtained by anthropometric measurement based on the z-score weight-for-age index. Caregiving behaviors that consist of attention to the mothers and feeding practices were poor, while home health practices were adequate. Most of the nutritional status of children under five was good (57.1%). Correlation analysis showed that attention to the mothers (r=0.321; p<0.05), feeding practices (r=0.252; p<0.05) and home health practices (r=0.358; p<0.05) were related positively to nutritional status. The study showed that caregiving behavior that affects nutritional status was attention to the mothers, feeding practices and home health practices.